Sustainable Click: An online game that boosts entrepreneurship and sustainable development - Aguillar, Eduardo; Imperador, Adriana Maria; de Mello Filho, Marco Antônio; Barbosa Silva, Leonardo; Ferreira Santos, Mayara; Franco Severino, Matheus (Guará Journal, 2017)
In order to promote sustainable development, the Brazilian Federal Government has been given priority to investments in key areas such as Science and Technology. Efforts have been made to stimulate entrepreneurship among future environmental engineers by including several lectures about business and management in their curriculum. The present work collects the activities of a team composed by professors and undergraduate students of the Environmental Engineering course from the Science and Technology Institute of Alfenas Federal University, working in collaboration with students and teachers from the school Dr. José Vargas de Souza. The main goal of the team was to design and to deploy a site hosting an online game that defies the player to successfully manage one among a limited set of fictitious businesses while taking into account the possible impacts and risks on the environment. Noteworthy is the enthusiasm aroused in high school students who, hopefully, will act as multipliers among their peers.